The effect of intermediate stop and ball size in fabrication of recycled steel powder using ball milling from machining steel chips - Mohd Fitri Mohamad Wahid; C.H. Shun; Shaiful Rizam Shamsudin; Shamsul Baharin Jamaludin (Universiti Teknologi Malaysia (UTM), 2008)
Organized by Universiti Teknologi Malaysia (UTM), 28th - 30th November 2007 at Johor Bahru, Johor.